Primary pulmonary neoplasia in cats: assessment of computed tomography findings and survival. (30th September 2015) - Nunley, J.; Sutton, J.; Culp, W.; Wilson, D.; Coleman, K.; Demianiuk, R.; Schechter, A.; Moore, G.; Donovan, T.; Schwartz, P.
Abstract : OBJECTIVE: To identify variables with a preoperative computed tomography scan that influence survival of cats undergoing surgical removal of a primary lung tumour. A secondary objective was to determine whether histologic type and or grade of feline pulmonary tumours affects long term survival. METHODS: Medical records were retrospectively reviewed for cats with preoperative computed tomography scans and surgical resection of primary lung tumours. Pulmonary carcinomas were reviewed for histologic diagnosis using two different approaches, histologic grade as well as major histologic pattern. RESULTS: Median survival time of all (n = 28) cats was 156 days. Median survival time for cats with lymph node enlargement was 65 days versus 498 days for cats without lymph node enlargement on preoperative computed tomography scan. Median survival time for cats with preoperative pleural effusion was 2 · 5 days versus 467 days for cats without pleural effusion. Cats with low or intermediate grade tumours had a median survival time of 730 days versus 105 days for cats with high grade tumours. CLINICAL SIGNIFICANCE: Cats with preoperative lymph node enlargement and pleural effusion have shorter survival times than cats without.